1994
DOI: 10.1139/m94-003
|View full text |Cite
|
Sign up to set email alerts
|

Production, purification, and characterization of an extracellular endo-β-1, 3-glucanase from a monokaryon of Schizophyllum commune ATCC 38548 defective in exo-β-1, 3-glucanase formation

Abstract: 1994. Production, purification, and characterization of an extracellular endo-a-l,3-glucanase from a monokaryon of Schizophyllum commune ATCC 38548 defective in exo-P-1,3-glucanase formation. Can. J. Microbiol. 40: 18-23. Production of extracellular P-1,3-glucanase activity by a monokaryotic Schizophyllum commrtne strain was monitored and results indicated that the P-glucanase activity consisted of an endo-P-l,3-glucanase activity, besides a negligible amount of P-1,6-glucanase and P-glucosidase activity. Unli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
(19 reference statements)
4
5
0
Order By: Relevance
“…The affinity of the 75-kDa glucanase for laminarin is among the highest reported in the literature. The K m value of 20 µg·mL -1 is similar to that found for T. longibrachiatum (16 µg·mL -1 ) (Tangarone et al 1989) and lower than those observed for the 94-kDa glucanase from Stachybotrys elegans (180 µg·mL -1 ) (Tweddell et al 1995) and for glucanases obtained from Penicillium italicum (40 µg·mL -1 ) (Sanchez et al 1982), Schizophyllum commune ATCC 38548 (280 µg·mL -1 ) (Prokop et al 1994), and T. harzianum (1180 µg·mL -1 ) (Noronha and Ulhoa 1996).…”
Section: Biological Activitysupporting
confidence: 77%
“…The affinity of the 75-kDa glucanase for laminarin is among the highest reported in the literature. The K m value of 20 µg·mL -1 is similar to that found for T. longibrachiatum (16 µg·mL -1 ) (Tangarone et al 1989) and lower than those observed for the 94-kDa glucanase from Stachybotrys elegans (180 µg·mL -1 ) (Tweddell et al 1995) and for glucanases obtained from Penicillium italicum (40 µg·mL -1 ) (Sanchez et al 1982), Schizophyllum commune ATCC 38548 (280 µg·mL -1 ) (Prokop et al 1994), and T. harzianum (1180 µg·mL -1 ) (Noronha and Ulhoa 1996).…”
Section: Biological Activitysupporting
confidence: 77%
“…β‐1,3‐Glucanases of low molecular mass have also been reported previously in different fungi [1]. Values of 29.0, 32.1 and 35.5 kDa have been obtained for Rhizoctonia solani, Rhizopus arrhizus QM 1032 and Schizophyllum commune ATCC 38548 [14–16], respectively.…”
Section: Resultssupporting
confidence: 73%
“…Future gene (mRNA) isolation and sequencing as well as genome analyses have to enlighten this issue further. Thus far, molecular weights of endoglucanases from various white‐rot fungi range from 15.5 to 65 kDa, as summarized in Table .…”
Section: Discussionmentioning
confidence: 99%